واقع التخطيط الاستراتيجي في جامعة تشرين من وجهة نظر العاملين فيها - شرف, سمير; عامر, وليد; عطيرة, عبير (Latakia University Journal - Economic and Legal Sciences Series, 2019)
هدف البحث إلى بناء أنموذج لمراحل التخطيط الاستراتيجي في جامعة تشرين، استناداً إلى الأدب النظري المتعلق بالتخطيط الاستراتيجي، وبناء على إجابات أفراد عينة البحث من العاملين الإداريين والأكاديميين في الجامعة على إمكانية تطبيق مراحل عملية التخطيط الإستراتيجي. تبعاً لمتغيري (المؤهل العلمي، الخبرة). اشتملت عينة البحث على (80) عاملاً إدارياً وعلمياً للعام 2009- 2010. ولتحقيق هذا البحث صممت استبانة احتوت على (55) عبارة وزعت إلى ست مراحل لعملية التخطيط الاستراتيجي وهي: (مرحلة التخطيط، مرحلة التحليل، مرحلة الاتجاه، مرحلة الصياغة، ومرحلة التنفيذ، وأخيراً مرحلة الضبط). وأظهرت نتائج البحث أن درجة تطبيق مراحل عملية التخطيط الإستراتيجي من قبل الإداريين والأكاديميين في جامعة تشرين كانت متوسطة في جميع مراحل عملية التخطيط الإستراتيجي، وعدم وجود فروق بين الإداريين والأكاديميين تبعاً لمتغيري المؤهل العلمي، الخبرة. قدم البحث مقترحات منها أن تتبنى جامعة تشرين التخطيط الاستراتيجي كأداة من أدوات التغيير في تطوير العمل الإداري. The research aimed at building a strategic planning model for Tishreen University, based on the theoretical literature of strategic planning, and on the answers of research sample of administrators and academics about the degree of Application Strategic Planning Stages at university according to the variables (qualification, and experience).The sample included 80 administrative members in the academic year 2009/2010. To achieve the object of the research, a questionnaire has included (55) items, distributed to six Stages for Strategic Planning (Planning, Analysis, direction, forging, enforcement, and the control). The findings were the following: The degree of implementation of the stages of strategic planning in Tishreen University by administrators and academics was average in all phases of the strategic planning process. In fact, there are differences between the administrators and academics in qualification and experience. The Research has finally presented suggestions concerning Tishreen University that it must adopt strategic planning as a tool for changing and developing administrative work.